Motivational interviewing training for medical students: A pilot pre-post feasibility study. Issue 11 (November 2018) - Chéret, Antoine; Durier, Christine; Noël, Nicolas; Bourdic, Katia; Legrand, Chantal; D'Andréa, Catherine; Hem, Evelyne; Goujard, Cécile; Berthiaume, Patrick; Consoli, Silla M.
Highlights: The effects of brief training in motivational interviewing (MI) for medical students were evaluated. Medical students showed a clear improvement in MI skills. There was a modest improvement in the students' empathy, as perceived by the 'patients'. MI training by a non-specialist professional is feasible early in medical courses. These results encourage the implementation of MI training during medical studies. Abstract: Objective: To evaluate the impact of brief training in motivational interviewing (MI) from a non-specialist professional for medical students. Methods: Students ( n  = 20) received three four-hour sessions of MI training over one week. They interviewed caregivers acting as patients in two standardised medical situations, six weeks before and three weeks after training. Global scores from the MITI-3.1.1 code, including "MI- Spirit", were attributed to the audiotaped interviews by two independent coders, blind the pre- or post-training status of the interview. Secondary outcomes were: caregivers' perception of students' empathy (CARE questionnaire), students' evaluation of self-efficacy to engage in a patient-centred relationship (SEPCQ score), and students' satisfaction with their own performance (analogue scale). Results: MI-Spirit score increased significantly after training ( p  < 0.0001, effect size 1.5). Limited improvements in CARE score ( p  = 0.034, effect size 0.5) and one of the SEPCQ dimensions (sharing information and power with the patient; p  = 0.047, effect size 0.5) were also noted. Students' satisfaction score was unaffected ( p  = 0.69). Conclusion: These findings suggest that brief MI training can improve communication skills in medical students. Practice implications: Such an intervention is feasible and could be generalised during medical studies.